2012
DOI: 10.1210/er.2011-1044
|View full text |Cite
|
Sign up to set email alerts
|

All Bariatric Surgeries Are Not Created Equal: Insights from Mechanistic Comparisons

Abstract: Despite considerable scientific progress on the biological systems that regulate energy balance, we have made precious little headway in providing new treatments to curb the obesity epidemic. Diet and exercise are the most popular treatment options for obesity, but rarely are they sufficient to produce long-term weight loss. Bariatric surgery, on the other hand, results in dramatic, sustained weight loss and for this reason has gained increasing popularity as a treatment modality for obesity. At least some sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
207
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(218 citation statements)
references
References 234 publications
11
207
0
Order By: Relevance
“…[94][95][96][97][98][99][100][101][102] Head-tohead comparisons of metabolic impact confirm the superiority of malabsorptive over gastric volume reduction surgeries, albeit at the expense of a greater perioperative risk and higher likelihood of malnutrition. However, meta-analyses of the LAGB versus RYGB data highlight the excess of late (≥30 days) complications and the need for reoperation for LAGB patients.…”
Section: Comparison Among Bariatric Proceduresmentioning
confidence: 86%
“…[94][95][96][97][98][99][100][101][102] Head-tohead comparisons of metabolic impact confirm the superiority of malabsorptive over gastric volume reduction surgeries, albeit at the expense of a greater perioperative risk and higher likelihood of malnutrition. However, meta-analyses of the LAGB versus RYGB data highlight the excess of late (≥30 days) complications and the need for reoperation for LAGB patients.…”
Section: Comparison Among Bariatric Proceduresmentioning
confidence: 86%
“…An accumulating body of research in animal models corroborates many of the feeding behavior changes observed following RYGBP (105). However, these animal studies should be interpreted with caution due to important differences in the rodent stomach and rodent feeding behavior (106,107), both of which could adversely affect interpretation of RYGBP-induced outcomes.…”
Section: Insights From Animal Modelsmentioning
confidence: 99%
“…Additionally, gender-specific mechanistic studies involving genotype-stratified and obesity phenotype-matched subjects would greatly enhance this field of research. Studies comparing RYGBP with SG, another metabolic procedure with differential biological effects from those of RYGBP (66,88,105,127,128), might also yield important insights into the mechanisms underlying the changes in food preference, hedonic feeding, and neural responsivity. Future research might also employ these bariatric procedures, using a Mendelian randomization experimental approach, as a tool to probe the physiological and genetic mechanisms underlying obesity.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…We recommend a recent review by Stefater et al, which provides an extensive discussion on the current understanding of the mechanisms of RYGB, LAGB, and LSG [27]. Interstingly, they propose that current evidence shows LSG to be more similar in action to RYGB, rather than LAGB.…”
Section: Potential Mechanisms For Rygb-related T2dm Improvementmentioning
confidence: 98%